2016
DOI: 10.1186/s40792-016-0265-z
|View full text |Cite
|
Sign up to set email alerts
|

Giant insulinoma: report of a case and review of published reports

Abstract: BackgroundLarger insulinomas are reportedly more likely to be malignant; however, their biological behavior has not been clearly elucidated. We here report the characteristics and treatment of a giant insulinoma with local invasion and lymph node metastasis. We also review published reports concerning the clinical features of giant insulinomas and comparing their grading with that of pancreatic neuroendocrine tumors.Case presentationA 71-year-old man was referred to our hospital for investigation of persistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Several studies have reported large insulinomas to be malignant more often, and the late symptomatology suggests relatively low or acquired insulin production (Fig. 2) [1,38,39]. The ARX transcription factor is not expected to be expressed in insulinomas [40], as it is not expressed in pancreatic beta-cells [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported large insulinomas to be malignant more often, and the late symptomatology suggests relatively low or acquired insulin production (Fig. 2) [1,38,39]. The ARX transcription factor is not expected to be expressed in insulinomas [40], as it is not expressed in pancreatic beta-cells [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Nfe2l1-deficient insulinoma cells show a marked chemotherapeutic resistance through the HK1-mPTPrelated metabolic pathway. The fact that Nfe2l1 deficiency in inoculated cells resulted in a more rapid tumor growth and aggressiveness potentially indicates an impact on tumor progression as recent evidence indicates that larger insulinomas are more frequently malignant than smaller ones (Ueda et al 2016). This study provides additional evidence that NFE2L1 is involved in chemotherapeutic resistance and indicates NFE2L1 modulation could be an important therapeutic target in the future to help prevent or cure certain cancers.…”
Section: :3mentioning
confidence: 57%
“…In vitro, the Nfe2l1-KD MIN6 cells were also hyperproliferative, showed enhanced migration/ invasiveness and displayed chemotherapeutic resistance. In this regard, recent clinical evidence indicates that larger insulinomas more frequently show malignant characteristics, such as local invasion or metastasis to the liver, than smaller tumors (Ueda et al 2016). The drug resistance from Nfe2l1-KD deficiency appeared to be due to resistance to chemotherapeutic-induced mitochondrial damage and was due to upregulation of HK1, which was localized in mitochondria and caused mPTP closure.…”
Section: Figurementioning
confidence: 98%
“…In a benign process, surgical treatment in most cases contributes to complete remission of the disease (relapse is no more than 3%); in the case of a malignant type of insulin-producing tumor in 2/3 of cases metastasis is not observed [3]. At the same time, in case of the metastatic liver lesion, the average survival rate of patients does not exceed several years [4]. The diagnosis of malignant insulinoma in our patient was obvious and established more than 10 years ago and the features of the clinical picture, which deserve the attention of internists and endocrinologists, first of all, were determined by difficulties in correcting of severe recurrent hypoglycemia against the background of a steady progression of the underlying disease despite the polychemotherapy (PCT) and sevenfold appliance of high-tech care, embolization and chemoembolization (CE) of the hepatic arteries.…”
Section: Introductionmentioning
confidence: 99%